Religiosity sebagai Pemoderasi Pengaruh Debt Covenant dan Profitability terhadap Tax Avoidance: Studi pada Indeks Kompas 100 di Bursa Efek Indonesia - Leonartan Leonartan (LPPM Universitas Widya Dharma Pontianak, 2025)
This study aims to analyze the influence of debt covenants and profitability on tax avoidance, using religiosity as a moderating variable. The research employs a causal associative approach. This study focuses on a population of companies included in the Kompas 100 Index and listed on the Indonesia Stock Exchange from 2019 to 2023. A sample of 37 companies was selected using purposive sampling, resulting in 185 observational data sets. The data used are secondary data in the form of company financial reports and information on the list of sharia-compliant securities. Data analysis tools used were IBM SPSS version 26 software. Data analysis techniques included descriptive statistical analysis, classical assumption testing, multiple linear regression analysis, moderated regression analysis (MRA), and hypothesis testing. The results indicate that debt covenants have a negative effect on tax avoidance, while profitability has no effect. The moderation results indicate that religiosity does not moderate the effect of debt covenants and profitability on tax avoidance.